Develop Technology Based Multimedia For Indonesian Teachers - Muslimat, Ade; Muhsin, Hadijah; Wahid, Hariyaty Ab; Yulistiana, Ika; Susilawati; Sunarsi, Denok; Dewi, R. Roro Vemmi Kesuma; Ilham, Dodi (The journal of contemporary issues in business and government, 2021)
Good learning must make the most of the learning media for support the achievement of learning objectives. However, not all teachers are able to make and using computer-based multimedia. The purpose of this research is to find out multimedia user experience using the latest technology for Professional Education Teacher . This study uses a quantitative approach respondent are 22 teachers, collected data using Google Form accordingly instrument and worked on within 10-15 minutes, then analyzed the mean, variance and Standard Deviation uses the ueq-online site. There are five research results from the UEQ test a scale that is categorized as Excellent, namely the Attractiveness, Efficiency, Dependability, Stimulation and Novelty. While the Perspicuity scale is categorized as Above Average accordingly with the UEQ benchmark interval. All average values above <0.08 indicate that evaluation of the experience of using multimedia is positive. The conclusion that learning multimedia using Media Studio's autoplay program is excellent - satisfying to use for Teacher Professional Education